Syntax as Meaning: The Stylistic Construction of the Past in American Feature Writing. (25th October 2020) - Garrisi, Diana
ABSTRACT: This paper explores the stylistic construction of the past in feature writing using as a case study the American Pulitzer Prize for journalism. Drawing on stylistic rhetorical criticism, it will show how references to the past are framed within fixed syntactical and word arrangement schemes that produce meaning and sustain arguments through expressive and aesthetic effects. The stylistic devices identified include comparative parallelism, series, emphatic repetition and syntactic symbolism. This paper contends that references to the past in feature writing should be seen as literary artefacts constructed by following the rules of rhetorical stylistics. The understanding of the uses of history that we can obtain from reading references to the past in journalism cannot be separated from formal and structural aspects pertaining to sentence patterns. Embedding rhetorical schemes in the text pushes the force of language beyond its representational role by bringing forward its expressive and evocative characteristics and the role that these play in making the story unique and memorable. The use of history in journalism goes beyond representing a given historical fact; the form through which the fact is presented matters because it makes each historical record discursively unique, thus contributing to the news value of the story.